Experimental Study of The Use of Spiderman Game Media (Spinner of Education for Mankind) In Learning Sociology for Improving Student Learning Outcomes - Anna Rusmiyati (Metafora: Education, Social Sciences and Humanities Journal, 2021)
The aim of this research is to: (1) be able to vary the methods of learning in the classroom, (2) create fun and enjoyable learning by using spiderman games. That way it can make it easier to understand and comprehend learning material so that it improves student learning outcomes in sociology subjects at SMA Negeri 1 Pulung. This study uses a quasi experimental design method (quasi-experimental) with a form of nonequivalent control group design. The population in this study were students of class XI IPS (social science) 1 and XI IPS (social science) 3 of SMA Negeri 1 Pulung, totaling 68 students. The sample used in this study was the entire population, namely two classes from class XI of the IPS (social science) program. All class, divided to, one class is grouped into an experimental class (35 students) and another class as a control class (33 students). The experimental class applies the "spiderman" learning media and the control class applies the power point learning media. This research data collection using tests and documentation. Data collected are pre-test and post-test. Data analysis techniques using quantitative descriptive. The results showed that: (1) based on the results of the calculation at the time of the pretest compared to the post test showed that the learning outcomes of the experimental class students increased from 45.16% to 80.7% who passed the KKM (minimum completeness criteria), while the learning outcomes of the control class from 20% when the pretest becomes 50% at the post test. Based on these results show evidence that learning media "spiderman" is better than learning media power point, (2) learning media "spiderman" has a significant influence on learning outcomes of students of class XI IPS (social science) in SMA Negeri 1 Pulung that is equal to 35.54%. With a positive number which means that the average post test value of the experimental class is greater than the control class. This shows that the learning media "spiderman" has an influence on improving student learning outcomes in sociology subjects.